Clinical practice guidelines for the diagnosis and management of otitis media with effusion (OME) in children in Japan, 2015. Issue 5 (October 2017) - Ito, Makoto; Takahashi, Haruo; Iino, Yukiko; Kojima, Hiromi; Hashimoto, Sho; Kamide, Yosuke; Kudo, Fumiyo; Kobayashi, Hitome; Kuroki, Haruo; Nakano, Atsuko; Hidaka, Hiroshi; Takahashi, Goro; et al.
Abstract: Objective: To (1) indicate the definition, the disease state, methods of diagnosis, and testing for otitis media with effusion (OME) in childhood (<12 years); and (2) recommend methods of treatment in accordance with the evidence-based consensus reached by the Subcommittee of Clinical Practice Guideline for Diagnosis and Management of OME in Children. Methods: We produced Clinical Questions (CQs) concerning the treatment of OME and searched the literature published until April 2014 according to each theme including CQ, the definition, the disease state, the method of diagnosis, and examination. The recommendations are based on the results of the literature review and the expert opinion of the Subcommittee. Results: Because children with Down's syndrome and cleft palate are susceptible to OME, we categorized OME into low-risk and high-risk groups (e.g., Down's syndrome and cleft palate), and recommended the appropriate treatment for each group. Conclusion: In the clinical management of OME in children, Japanese Clinical Practice Guidelines recommend management not only of OME itself, such as effusion in the middle ear and pathological changes in the tympanic membrane, but also pathological abnormality in surrounding organs, such as infectious or inflammatory diseases.